Evaluation of Acid-Base Accounting to Predict the Acid Water of Overburden in Coal Mines in Horna Areas, West Papua Province, Indonesia - Hamdani, Ahmad Helman; Hutabarat, Johanes; Haryanto, Iyan; Ilmi, Nisa Nurul (Journal of Geological Sciences and Applied Geology, 2017)
Acid-Base Accounting (ABA) is an analytical procedure to measure the balance between the acid neutralization and acid generation properties of any geologic material. ABA is considered tools  to predict post-mining water. Overburden samples were collected from the coalfields of Horna coalmines. Maximum potential acidity (MPA), acid neutralizing capacity (ANC), acid net neutralization potential (ANG), Net Acid Producing Potential  (NAPP), net acid generation (NAG), and ANC/MPA ratios were determined for each site based on ABA.  Most of the sample from R1, R4, R-13, and R14 showing the pH of net acid generation of overburden ranges from 3.2 – 4.47 and positively acid net neutralization potential (be classified as the PAF-LC (Low Capacity Potential Acid NAPP) varies from 2.07 – 21.27 2.4 kg/t H2SO4   indicate that the samples are classified as the PAF-LC (Low Capacity Potential Acid Former (LC-PAF) to the PAF-MC (Moderately Capacity Potential Acid Former (MC-PAF). Other samples from R13 (four samples) has negatively NAPP and pHNAG between 6,21 – 7,10, therefore should be classified as the NAF; two samples from R13 indicated the uncertainty (UC) due to high pHNGA (6,82-7,15).